Tratamiento con Manzanilla (Matricaria chamomilla), para reducción de las ojeras. - Jiménez Delgado, Jefrey (2009)
Objective:  Study the effect of the chamomile in the dark rings under the eyes and in the swelling in the periocular zone.Methodology:  Study in parallel (n=15), subjects were randomized to topical treatment or control in a proportion 2:1 respectively. To measure the results, was used a scale of tonality using Macromedia Fireworks and a test to all the subjects in study.The statistical analysis was using the software Epi Info® version 3.3. The data was analyzed with percentages and with a Test of Fisher with estimate of OR.Results: 70% of the individuals of the group intervention considered effective the treatment, as regards the tonality and volume of the dark rings under the eyes, 80% felt main relaxation in the periocular zone. Obtained OR=16; CI 95%= (0.75 – 760.46); p= 0.046 for the reduction of the tonality of the dark rings under the eyes.Conclusions:  No statistical significant difference was found in the decrease of the dark rings under the eyes; however a decrease is observed.